Optimization of SIM Services by Karawang Police Satpas to Realize Community Satisfaction - Alfaisar, Fantri (Indonesian Journal of Police Studies, 2024)
SIM is a must for every Indonesian citizen who drives a motorized vehicle. However, in the process of issuing SIM, there are still many irregularities and poor service quality. Lack of socialization to the community also causes ignorance of the public regarding information related to making SIM so this is often used by officials who are not responsible for making irregularities in making SIM. The theory used in this research is based on the management theory by George R. Terry, service theory by the sinambela of the concept of public services, the concept of MIS, and Law No. 22 of 2009 concerning Road Traffic and Transport and Law No. 25 of 2009 concerning Public Services. In this study the authors used a qualitative approach with field research methods. Data sources used are primary and secondary data sources. Data collection techniques used in this study were interviews, observation, and study of documents. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study found that SIM services at SATPAS Karawang Police were not optimal. SATPAS Karawang Regional Police still encountered many obstacles in providing services for the SIM applicant community, both from internal factors consisting of HR Police, Budget, facilities and infrastructure, and Technology as well as external factors namely the social conditions of the community. The steps taken by the Karawang Police SATPAS in optimizing services to the public are by implementing the FIFO (First In First Out) system.